(untitled) (Academia Journal of Medicine, 2024)
An implant-supported restoration in the anterior zone must produce the best possible aesthetic outcome. Providing rapid interim restorations after implant surgery has been suggested as a preferable course of therapy in the aesthetic zone. Following implant implantation, a well contoured interim restoration reduces alterations to the hard and soft tissues surrounding the implant. The aesthetic result and, thus, patient satisfaction may be improved as a result. To get the desired outcome, several prosthetic and surgical components must be properly designed and carried out. This case report describes the immediate loading of a single implant in the aesthetic zone.